The Impact of Information Technology Adoption on Efficiency and Transparency in Public Procurement Processes in Kenya - Nebert Ombajo Mandala; Isaac Renson Ayoyi; Samson Kipketer Too (European Scientific Journal, ESJ, 2024)
The study addresses a critical gap in existing knowledge by delving into the nuanced impacts of technological advancements on the intricate dynamics of public procurement in Kenya. The investigation meticulously examined the influence of technology adoption on efficiency and transparency, exploring a spectrum of experiences, challenges, successes, and overall implications within the procurement landscape. The study was anchored on the Technology Acceptance Model (TAM) and the Technology, Organization, and Environment (TOE) theory. The study adopted both quantitative and document analysis approaches. Data was collected using questionnaires and various literature reviews were carried out. The findings showed that IT usage and IT reliance collectively explain 26.5% of the variance in Efficiency and Transparency in public procurement, as indicated by the R Square value of .265.  The regression coefficient results lead to the rejection of both null hypotheses, indicating that both IT usage and IT reliance have significant effects on Efficiency and Transparency in public procurement. With p-values of 0.027 and 0.000, respectively, for IT usage and IT reliance, both are found to be statistically significant at the 0.05 level. This study concludes that IT plays a crucial role in enhancing the efficiency and transparency of public procurement processes, highlighting the importance of continued investment and integration of IT solutions in procurement practices to promote good governance and accountability. This study recommended that the government should Invest in IT Infrastructure, Enhance IT Training and Capacity Building, Ensure Data Security and Privacy, Monitor and Evaluate IT Performance and Promote Stakeholder Engagement in order to achieve efficiency and transparency in public procurement processes. By embracing the recommendations derived from this study, Kenya has the opportunity to navigate challenges and harness the potential of technology for a future marked by efficiency, transparency, and resilience in public procurement. The study aligns with the United Nations Sustainable Development Goals, and its outcomes contribute to the broader discourse on leveraging technology for positive transformations in public procurement practices.